Activation of the unfolded protein response in high glucose treated endothelial cells is mediated by methylglyoxal - Irshad, Z; Xue, M; Ashour, A; Larkin, JR; Thornalley, PJ; Rabbani, N (Springer Nature, 2019)
Metabolic dysfunction of endothelial cells in hyperglycemia contributes to the development of vascular complications of diabetes where increased reactive glycating agent, methylglyoxal (MG), is involved. We assessed if increased MG glycation induced proteotoxic stress, identifying related metabolic drivers and protein targets. Human aortal endothelial cells (HAECs) were incubated in high glucose concentration (20 mM versus 5 mM control) in vitro for 3-6 days. Flux of glucose metabolism, MG formation and glycation and changes in cytosolic protein abundances, MG modification and proteotoxic responses were assessed. Similar studies were performed with human microvascular endothelial HMEC-1 cells where similar outcomes were observed. HAECs exposed to high glucose concentration showed increased cellular concentration of MG (2.27 ± 0.21 versus 1.28 ± 0.03 pmol/106 cells, P < 0.01) and formation of MG-modified proteins (24.0 ± 3.7 versus 14.1 ± 3.2 pmol/106 cells/day; P < 0.001). In proteomics analysis, high glucose concentration increased proteins of the heat shock response - indicating activation of the unfolded protein response (UPR) with downstream inflammatory and pro-thrombotic responses. Proteins susceptible to MG modification were enriched in protein folding, protein synthesis, serine/threonine kinase signalling, glycolysis and gluconeogenesis. MG was increased in high glucose by increased flux of MG formation linked to increased glucose metabolism mediated by proteolytic stabilisation and increase of hexokinase-2 (HK-2); later potentiated by proteolytic down regulation of glyoxalase 1 (Glo1) - the major enzyme of MG metabolism. Silencing of Glo1, selectively increasing MG, activated the UPR similarly. Silencing of HK-2 prevented increased glucose metabolism and MG formation. trans-Resveratrol and hesperetin combination (tRES-HESP) corrected increased MG and glucose metabolism by increasing expression of Glo1 and decreasing expression of HK-2. Increased MG glycation activates the UPR in endothelial cells and thereby may contribute to endothelial cell dysfunction in diabetic vascular disease where tRES-HESP may provide effective therapy.